Comparison of Volatile Oxidation Products of Lard from Native Breed and Three-way Crossbred Breed Under Accelerated Oxidative Conditions - Xu, Yongxia; Zhao, Honglei; Meng, Liangyu; Fan, Gang; Chen, Qingchan; Pan, Siyi (Asian Journal of Chemistry, 2012)
The volatile composition of thermally oxidized lard from different sources was investigated. Volatile oxidation products extracted by headspace-solid phase micro-extraction were analyzed by gas chromatography-mass spectrometer. Fatty acid compositions in the lard of Enshi No.1 native breed (ENL) and three-way crossbred breed (TCL) were also determined. The contents of volatile oxidation products were higher in the ENL than in the TCL. Aldehydes were detected to be the most abundant volatile oxidation compounds in the two lard sources, representing from 72.37 to 73.77 %. Lard source had a significant (P < 0.05) influence on the major oxidation products of aldehydes, such as heptanal, octanal, nonanal, (E)-2-heptenal, (E)-2-octenal, (E, E)- 2, 4-heptadienal, (E, E)-2, 4-decadienal, 2-undecenal and so on. Only slight differences in other lipid oxidation products were observed.